Semiotic Analysis of Self-Identity Representation on TikTok @dokterdetektif Account - Nana Sutisna; Dina Nurfadilah (MID Publisher International, 2024)
TikTok has evolved into a digital communication platform that enables individuals to construct and represent their identities through audiovisual content. One of the TikTok accounts attracting public attention is @dokterdetektif, which is recognized for its critical and educational content related to health issues and medical aesthetics. This study aims to analyze the representation of self-identity portrayed in the TikTok content of @dokterdetektif. The research employed a qualitative approach using Roland Barthes’ semiotic analysis method. Data were collected through observation and documentation of videos uploaded to the @dokterdetektif TikTok account. The analysis was conducted through the levels of denotation, connotation, and myth to interpret visual, verbal, and symbolic signs representing self-identity. The findings reveal that the @dokterdetektif account represents a self-identity characterized as critical, educational, courageous, and independent in delivering information to the public. This representation is constructed through assertive verbal language, visual expressions, persuasive communication styles, and symbols of professionalism displayed in the content. Furthermore, the constructed identity reflects an effort toward personal branding as a digital public figure with authority in health and social issues. This study demonstrates that TikTok functions not only as an entertainment platform but also as a space for identity construction and self-image formation in the digital communication era.